2015
DOI: 10.1002/jor.22921
|View full text |Cite
|
Sign up to set email alerts
|

Effects of corticosteroids and hyaluronic acid on torn rotator cuff tendons in vitro and in rats

Abstract: Corticosteroids (CS) or hyaluronic acid (HA) is used in subacromial injection for the conservative treatment of rotator cuff tears (RCT); this study addresses the question of how CS and HA affect the tendon tissue and fibroblasts in vitro and in rats. Cell proliferation assays were performed in human tendon fibroblasts from RCT. Rats underwent surgery to create RCT, and the surgical sites were injected with CS or HA. The rotator cuff tendons were subjected to biomechanical testing, microscopic and immunohistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 40 publications
0
41
0
1
Order By: Relevance
“…The results of several systematic reviews and meta-analyses over decades suggest there may be short-term symptomatic relief after CSI, but these results are often difficult to reproduce [4][5][6][7][8] . In addition, case reports from the past have suggested a correlation of CSI and tendon rupture [19][20][21] , which has been confirmed in multiple animal models 6,9,10,22 . Previous studies have also shown an increase in post-operative infection rates in patients who received pre-or peri-operative CSI's [23][24][25] , but recent systematic reviews and meta-analyses have challenged these claims 11,13,26,28 .…”
Section: Discussionmentioning
confidence: 96%
“…The results of several systematic reviews and meta-analyses over decades suggest there may be short-term symptomatic relief after CSI, but these results are often difficult to reproduce [4][5][6][7][8] . In addition, case reports from the past have suggested a correlation of CSI and tendon rupture [19][20][21] , which has been confirmed in multiple animal models 6,9,10,22 . Previous studies have also shown an increase in post-operative infection rates in patients who received pre-or peri-operative CSI's [23][24][25] , but recent systematic reviews and meta-analyses have challenged these claims 11,13,26,28 .…”
Section: Discussionmentioning
confidence: 96%
“…The same study also conducted an experiment on the effects of CS and HA injections in rats. Like the in vitro study, the animal study found apoptosis in rotator cuff tendons, inhibition of cell proliferation, a delay in tendon healing, and decreased biomechanical strength in CS subjects [59].…”
Section: Injectionsmentioning
confidence: 88%
“…A 2015 in vitro study found that CS injections decreased cell proliferation in rotator cuff tendons, and the resulting strength of these tendons decreased as compared to the strength after HA injections [59]. The same study also conducted an experiment on the effects of CS and HA injections in rats.…”
Section: Injectionsmentioning
confidence: 99%
“…In a previous study, Li et al found out that polyethylene terephthalate (PET) artificial ligament grafts coated with sodium hyaluronate can enhance cell adhesion, facilitated cell growth, and suppressed the expression of inflammation-related genes relative to a pure PET graft for ACL reconstruction [21]. Another study done by Nakamura et al demonstrated that HA possesses anti-inflammatory and antiadhesive activities in tendon and synovial fibroblasts derived from RCT [22]. In addition, Salamanna et al find out that, after repeated peripatellar injections of HA to rats, a significantly higher proliferation rate and viability, along with increased synthesis of C-terminal-propeptide of type I collagen, fibronectin, aggrecan, tenascin-c, and matrix-metalloproteinase-3 show respect to control group [23].…”
Section: Discussionmentioning
confidence: 99%